Vertical Profiles of PM2.5 and O3 Measured Using an Unmanned Aerial Vehicle (UAV) and Their Relationships with Synoptic- and Local-Scale Air Movements - Hwang, Hyemin; Lee, Ju Eun; Shin, Seung A.; You, Chae Rim; Shin, Su Hyun; Park, Jong Sung; Lee, Jae Young (Remote Sensing, 2024)
The vertical air pollutant concentrations and their relationships with synoptic- and local-scale air movement have been studied. This study measured the vertical profiles of PM2.5 and O3 using an unmanned aerial vehicle during summer in South Korea and analyzed the characteristics of the measured profiles. To understand the impact of synoptic air movements, we generated and categorized the 48 h air trajectories based on HYSPLIT, and we analyzed how the vertical profiles varied under different categories of long-range transport. We found that the vertical PM2.5 concentration has a positive gradient with altitude when more polluted air was transported from China or North Korea and has negative gradient when cleaner air was transported from the East Sea. Unlike PM2.5, the O3 concentration did not depend significantly on the long-range transport scenario because of the short photochemical lifetime of O3 during summer. For local-scale air movements, we found no significant impact of local wind on the measured profiles.
Keywords: Aerial vehicle; Air movement; Diurnal variation; Long range transport; PM 2.5; Surface winds; Synoptic-scale; Unmanned aerial vehicle; air quality; diurnal variation; drone; long-range transport; surface wind; synoptic-scale; UAV; unmanned aerial vehicle